Biomarcadores Inflamatorios de la Periodontitis: Una Revisión de Alcance. (2024)
Periodontitis is recognized as a persistent inflammatory disorder of multifactorial origin, where it is characterized by an increase in bacterial plaque, leading to gum inflammation and degradation of the tissue that supports the teeth. This pathology compromises oral health and has been linked to several systemic conditions, including cardiovascular disorders and diabetes. This relationship is thought to be due to prolonged inflammation and an altered immune response in cases of periodontitis.